Non-Violence Family Education; Takhrīj Hadith About the Prophet Not Hitting His Wife in Musnad Aḥmad Bin Ḥanbal - Husna, Fitria Miftakhul; Ikhwanuddin, Mohammad; Panjalu, Gandhung Fajar (UIR Press, 2024)
In family relationships between husband and wife, particularly in times of disagreement, violent behavior often arises and is sometimes misinterpreted as being sanctioned by the Qur'an, such as in Sūrat al-Nisā': 34, where hitting a wife is considered acceptable. However, the historical life of Rasulullah reflects that the Prophet never struck his spouse. This study investigates the hadith reported in Musnad Aḥmad bin Ḥanbal that highlights this aspect of the Prophet's behavior. The research employs a qualitative approach through library research, utilizing the takhrīj hadīs method to examine the isnād and matan of selected hadiths. Additionally, content analysis is applied to interpret the findings within the context of non-violence in family education. The results indicate four authentic hadiths in Musnad Aḥmad bin Ḥanbal, emphasizing that Rasulullah never engaged in physical violence against women, including his wives. This research underscores the Prophet's exemplary conduct and its implications for fostering harmonious family relationships.